2017
DOI: 10.3139/217.3484
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Heat-Seal Properties of Biodegradable Polymers through Melt Blending

Abstract: In this study, we address heat-seal properties of poly (lactic acid) (PLA), blended with Poly (butylene adipate-co-terephthalate) (PBAT). The objective is to correlate blends crystalline structure and morphology to corresponding heat-seal of blends films. The SEM micrographs show a two-phase elongated morphology where stretched ellipsoids developed through elongational flow during the cast film process. To distinguish the effect of crystallization, we also prepared amorphous and crystalline PBAT films and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Moreover, interesting results of these blends are reported also for the food packaging field. Tabasi et al [35] reported that the sealability properties of PLA/PBAT blends can be tailored by varying the blend composition and PBAT crystallinity degree. Higher content of PLA in the blend and the lower crystallinity of PBAT provide lower hot-tack initiation temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, interesting results of these blends are reported also for the food packaging field. Tabasi et al [35] reported that the sealability properties of PLA/PBAT blends can be tailored by varying the blend composition and PBAT crystallinity degree. Higher content of PLA in the blend and the lower crystallinity of PBAT provide lower hot-tack initiation temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying cause of this shift is related to the crystalline structure of PBAT. A gradual decrease of PBAT crystallinity correlates with the shift in seal initiation temperature 112 …”
Section: Polyestersmentioning
confidence: 99%
“…Welding properties are important in food packages, but only few studies with bio based and/or biodegradable polymers are available in the literature (Tabasi and Ajji, 2017).…”
Section: Films Propertiesmentioning
confidence: 99%